The Impact of Emotional Intelligence on Citizenship Behavior of Physicians (With Emphasis on Infertility Specialists) - Elham Sahafi; Habibolah Danaee; Mohammad Sarlak; Fedyeh Haghollahi (Tehran University of Medical Sciences, 2011)
Objective: To survey emotional intelligence in promoting of the citizenship behavior (manner gesture) of physicians. Materials and methods: In a descriptive study, co relational and statistical community approach of research were used. Cases were doctors having subspecialty of the infertility in Islamic Republic of Iran. Using simple random sampling method 212 cases were selected. Questionnaire was used for data collection. After summarization, structural equation modeling techniques were used for analyses and interpretation of research data. Results: Findings confirmed that three of the five aspects of EI have had significant positive impact on the citizenship manner of physicians that these factors in order to their priority impact are: 1) Empathy, 2) Self motivation and 3) Self control. Conclusion:EI interpersonal elements have greater influence on the citizenship behavior of physicians.